Sosialisasi Literasi Media Digital bagi Kaum Muda Desa Oringbele Kecamatan Witihama Kabupaten Flores Timur - Benedicto Aprian Thaa; Yohanes Kornelius Ethelbert; Stephanie Perdana Ayu Lawalu; Frans Nyong; Yasinta Palan Peten (Syntax Corporation Indonesia, 2024)
The digital era has revolutionized the way people live, including in Oringbele Village, Witihama District, East Flores Regency. Ease of access to information through the internet opens up new opportunities, but also presents challenges. Digital media literacy is the key for young people to use technology wisely and responsibly. This journal examines the socialization of digital media literacy for the youth of Oringbele Village. This activity aims to improve their knowledge and skills in using digital media safely, critically, and creatively. Socialization was carried out by the method of material presentation, and discussion. The material presented included the definition of digital media literacy, the benefits and risks of digital media, digital media ethics, how to identify and avoid negative content, and tips for safe and responsible social media. The results of the socialization show that the level of digital media literacy of young people in Oringbele Village is still low. However, they are enthusiastic about learning and improving their ability to use digital media wisely. The socialization of digital media literacy provides significant benefits for the youth of Oringbele Village. This activity helps improve their knowledge and skills in using digital media wisely and responsibly. Further socialization and continuous assistance are needed to ensure that digital media literacy continues to develop in Oringbele Village.